Sonations in Migratory and Non-migratory Fork-tailed Flycatchers (Tyrannus savana) - Gomez-Bahamon, Valentina; Tuero, Diego T.; Castano, Maria Isabel; Jahn, Alex E. [UNESP]; Bates, John M.; Clark, Christopher J. (Oxford Univ Press Inc, 2020)
Sonations are sounds that animals produce with structures other than the vocal apparatus for communication. In birds, many sonations are usually produced with modified flight feathers through diverse kinematic mechanisms. For instance, aeroelastic fluttering of feathers produces tonal sound when airflow exceeds a threshold velocity and induces flight feathers to oscillate at a constant frequency. The Fork-tailed flycatcher (Tyrannus savana) is a Neotropical bird with both migratory and year-round resident subspecies that differ in the shape of the outer primary feathers of their wings. By integrating behavioral observations, audio recordings, and high-speed videos, we find that male Fork-tailed flycatchers produce sonations with their outer primary feathers P8-10, and possibly P7. These sounds are produced during different behavioral contexts including: the pre-dawn display, intraspecific territorial disputes, when attacking potential nest predators, and when escaping. By placing feathers in a wind tunnel, we elicited flutter at frequencies that matched the acoustic signature of sounds recorded in the wild, indicating that the kinematic mechanism responsible for sound production is aeroelastic flutter. Video of wild birds indicated that sonations were produced during the downstroke. Finally, the feathers of migratory (T.s.savana) and year-round resident (T.s.monachus) Fork-tailed flycatchers flutter in feather locations that differ in shape between the subspecies, and these shape differences between the subspecies result in sounds produced at different frequencies.